Using Boolean Satisfiability for Exact Shuttling in Trapped-Ion Quantum Computers - Schoenberger, Daniel; Hillmich, Stefan; Brandl, Matthias; Wille, Robert (Proceedings of the ASP-DAC ... Asia and South Pacific Design Automation Conference, 2024)
Trapped ions are a promising technology for building scalable quantum computers. Not only can they provide a high qubit quality, but they also enable modular architectures, referred to as Quantum Charge Coupled Device (QCCD) architecture. Within these devices, ions can be shuttled (moved) throughout the trap and through different dedicated zones, e.g., a memory zone for storage and a processing zone for the actual computation. However, this movement incurs a cost in terms of required time steps, which increases the probability of decoherence, and, thus, should be minimized. In this paper, we propose a formalization of the possible movements in ion traps via Boolean satisfiability. This formalization allows for determining the minimal number of time steps needed for a given quantum algorithm and device architecture, hence reducing the decoherence probability. An empirical evaluation confirms that-using the proposed approach-minimal results (i.e., the lower bound) can be determined for the first time. An open-source implementation of the proposed approach is publicly available at https://github.com/cda-tum/mqt-ion-shuttler.